Comparative Analysis of Plant-Related Verses from the Perspectives of Agus Purwanto and the Indonesian Ministry of Religious Affairs (Kemenag RI) Tafsir - Fahmi Ilmi Najil; Abdul Muhaimin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The advancement of science and technology demands interpretation of the Qur'an that remains relevant to contemporary times. As Muslims believe, the Qur'an is shalih fii kulli zaman wa makan—relevant for every time and place. The Qur'an not only contains verses of worship but also explicitly mentions plants as evidence of Allah's power and as sources of benefit for all living beings. This study aims to comparatively analyze the interpretations of Agus Purwanto and the Kemenag RI Tafsir regarding plant-related verses, as well as to identify their similarities and differences. The method used is qualitative-comparative (muqaran) with a library research approach. Primary sources include Agus Purwanto's works (Ayat-Ayat Semesta and Nalar Ayat-Ayat Semesta) and the Al-Qur'an dan Tafsirnya by Kemenag RI. The results show that both explain the functions and benefits of plants scientifically, use the Indonesian language, and reflect on Allah's blessings. Differences lie in the scope of verses interpreted—Agus Purwanto focuses on Q.S. Al-Insan: 17 (ginger), while the Kemenag RI Tafsir covers more verses—as well as differences in interpreting the taste and origin of ginger.